Fresno-Merced Counties Legal Services Christmas Party at Patience Milrod's Home - Watkins, Howard::::::::: (1980)
Attendees, Doris Burnes reading card, Tony White holding son, MaryBeth Riday holding other son 3400 Block of E. Montecito Avenue